Participatory Recontextualization of Wayang Serok Baros for Contemporary Relevance - Putri, Arum Githa; Soemardi, Arlene Dwiasti (Indonesian Journal of Computing, Engineering, and Design (IJoCED), 2026)
Rapid media transformation and fast-paced changes in youth preferences become the main challenge for community-based cultural practices. In Desa Baros, West Java, Wayang Serok becomes one of the representations of a living tradition with high potential as a medium of inspiration for cultural heritage activation. This study explores other approaches in safeguarding a heritage – to translate cultural narratives into contemporary forms that are relatable for younger generation (Generation Z). The research combines a Participatory Learning Action framework by integrating Design Thinking process as co-creation in character and merchandise design inspired by Wayang Serok symbolism. Data gathered from field observation with local cultural representatives was analyzed alongside a survey to design an engaging merchandise suitable for Gen Z’s preferences and cultural consumptions. The findings suggest that design intervention – stylized character interpretation and accessible personalized trinkets – can function as mediators between traditional narratives and contemporary youth identity expression. Exhibitions, feedback, and digital engagement indicate that narrative-driven accessories can build emotional attachment and curiosity toward the topic. This study also proposes a participatory design approach that may potentially broaden other inclusive approaches as strategies to recontextualize many intangible heritages in the economic and creative ecosystem.